Fusion primer driven racket PCR: A novel tool for genome walking - Pei, Jinfeng; Sun, Tianyi; Wang, Lingqin; Pan, Zhenkang; Guo, Xinyue; Li, Haixing (Frontiers in Genetics, 2022)
The limitations of the current genome-walking strategies include strong background and cumbersome experimental processes. Herein, we report a genome-walking method, fusion primer-driven racket PCR (FPR-PCR), for the reliable retrieval of unknown flanking DNA sequences. Four sequence-specific primers (SSP1, SSP2, SSP3, and SSP4) were sequentially selected from known DNA (5'→3′) to perform FPR-PCR. SSP3 is the fragment that mediates intra-strand annealing (FISA). The FISA fragment is attached to the 5′ end of SSP1, generating a fusion primer. FPR-PCR comprises two rounds of amplification reactions. The single-fusion primary FPR-PCR begins with the selective synthesis of the target first strand, then allows the primer to partially anneal to some place(s) on the unknown region of this strand, producing the target second strand. Afterward, a new first strand is synthesized using the second strand as the template. The 3′ end of this new first strand undergoes intra-strand annealing to the FISA site, followed by the formation of a racket-like DNA by a loop-back extension. This racket-like DNA is exponentially amplified in the secondary FPR-PCR performed using SSP2 and SSP4. We validated this FPR-PCR method by identifying the unknown flanks of Lactobacillus brevis CD0817 glutamic acid decarboxylase genes and the rice hygromycin gene.